Osteohistological correlates of muscular attachment in terrestrial and freshwater Testudines - Pereyra, María Eugenia (2019)
Sharpey's fibers are considered the anatomical structures integrated to the muscles. Since these fibers leave marks at the microscopic level, their presence and distribution are used as evidence of muscle attachment in extinct and extant forms. In recent years, studies have been focusing on muscle-bone and tendon-bone interaction mostly on mammals. The main objective of this work is to contribute to the morphological and histological knowledge of muscle attachment in other amniotes, such as reptiles, and their variation related to different locomotor habits. In this way, a study was performed on terrestrial and aquatic turtles. The musculature related to the movement of the humerus, and pectoral girdle in Chelonoidis chilensis, Phrynops hilarii and Hydromedusa tectifera was analyzed. Dissections were performed mapping the origins and insertions of each muscle and undecalcified thin sections were performed in specific muscular attachment sites. We found some differences which were not previously reported, related to the insertion of the m. pectoralis, the m. coracobrachialis magnus and the origin of the m. tractor radii. The osteohistology revealed the presence of Sharpey's fibers in the cortex of all the bone elements analyzed. Patterns were established in relation to the orientation and density of Sharpey's fibers, which were used for the categorization of each muscle attachment site. The comparative micro-anatomical study of these areas did not reveal any important differences between terrestrial and freshwater turtles in muscles involved with the rotation, abduction and adduction of the humerus. In this way, the preliminary results suggest an absence of correlation between the distribution and density of Sharpey's fibers between different habitat forms, at least in the bones and species analyzed.